SPEED READING ACQUISITION IN READING TEXT - Siregar, Syahreni (Department of English Education of STAIN Jurai Siwo Metro, 2015)
Speed reading is how to get information that we need quickly without wasting time and do not need everything which is improve our speed reading.The objectives of this study are to investigate (1) how the readers approach and handle the texts, (2) whether or not students adjust their speeds when they read narrative and expository texts, (3) common problems faced by the readers when they have to use speed reading strategy. A qualitative approach was conducted to make a research on speed acquisition in reading texts through the analysis of the interview transcription of the students of senior high school class XII at Al-Azhar Medan.The ï¬ndings of the research indicate that (1) different texts need different approaches, techniques and strategies; the readers didnât apply strategy to read, probably they didnât know how to approach the texts. (2) the students did not adjust their speeds because they found many difï¬culties, and (3) the students got the problems on the level of language and ideas.Â Keywords: Reading speed, reading text